Kinetic modeling and long‐term test‐retest reproducibility of the mGluR5 PET tracer 18F‐FPEB in human brain. Issue 4 (8th February 2016) - Leurquin‐Sterk, Gil; Postnov, Andrey; de Laat, Bart; Casteels, Cindy; Celen, Sofie; Crunelle, Cleo L.; Bormans, Guy; Koole, Michel; Van Laere, Koen
ABSTRACT: 18 F‐FPEB is a promising PET tracer for studying the metabotropic glutamate subtype 5 receptor (mGluR5) expression in neuropsychiatric disorders. To assess the potential of 18 F‐FPEB for longitudinal mGluR5 evaluation in patient studies, we evaluated the long‐term test‐retest reproducibility using various kinetic models in the human brain. Nine healthy volunteers underwent consecutive scans separated by a 6‐month period. Dynamic PET was combined with arterial sampling and radiometabolite analysis. Total distribution volume ( V T ) and nondisplaceable binding potential (BPND ) were derived from a two‐tissue compartment model without constraints (2TCM) and with constraining the K 1 / k 2 ratio to the value of either cerebellum (2TCM‐CBL) or pons (2TCM‐PONS). The effect of fitting different functions to the tracer parent fractions and reducing scan duration were assessed. Regional absolute test‐retest variability (aTRV), coefficient of repeatability (CR) and intraclass correlation coefficient (ICC) were computed. The 2TCM‐CBL showed best fits. The mean 6‐month aTRV of V T ranged from 8 to 13% (CR < 25%) with ICC > 0.6 for all kinetic models. BPND from 2TCM‐CBL with a sigmoid fit for the parent fractions showed the best reproducibility, with aTRV ≤ 7% (CR < 16%) and ICC > 0.9 in most regions. Reducing the scan duration from 90 to 60 min did not affect reproducibility. These results demonstrate for the first time that 18 F‐FPEB brain PET has good long‐term reproducibility, therefore validating its use to monitor mGluR5 expression in longitudinal clinical studies. We suggest a 2TCM‐CBL with fitting a sigmoid function to the parent fractions to be optimal for this tracer. Synapse, 2016. © 2016 Wiley Periodicals, Inc. Synapse 70:153–162, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Using proper kinetic modeling, the authors demonstrate that 18 F‐FPEB, a promising PET radioligand for mGluR5, has high long‐term test‐retest reproducibility in healthy subjects. This finding validate the use of 18 F‐FPEB as a biomarker for longitudinal monitoring of mGluR5 in various neuropsychiatric disorders.